Between the Broad Daylight and the Shadow: Metamorphoses of the Bakhtiar Tale in Persian and Malay (Malay Literature, 2014)
Barthes defined the literary text as "a tissue of quotations drawn from the innumerable centres of culture". Developing this statement, we can postulate two forms of existence of the literary text. On the one hand, it may exist as a holistic entity in which all components are interlinked so that they can bear an integral meaning. This is a "syntagmatic" existence of the literary work as a "tissue", or a certain structure. On the other hand, the literary text may exist as a destructuralised set of the same components isolated from each other-its "paradigmatic" existence as a sum total of quotations that contribute to the all-embracing repository of "quotations", which makes up the intertext of a particular literature. This intertext provides "building blocks" for the construction of new literary pieces. In this article I shall discuss the two forms of existence of literary works on the basis of one piece of Persian literature translated into Malay. The example chosen is Hikayat Bakhtiar (Tale of Bakhtiar), and its transformations and diverse literary constructions that were built of "quotations" from it over more than two centuries. This discussion, among other things, will help us to explain the strong Persian influence on Malay traditional literature, despite the relatively small number of Persian writings translated into Malay.Keywords: traditional Malay literature, persian influence, Hikayat Bakhtiar, quotation, recension, intertext, Hikayat Maharaja Ali, Syair Bidasari